Calculation of own forms of fluid fluctuations in incompletely filled tanks (transverse oscillations) - Синеглазов, В. М.; Кеменяш, Ю. М. (Proceedings of National Aviation University (archive), 2020)
The method of solving problems of fluid fluctuations with the use of harmonics is developedfunctions. The principle of Hamelton-Ostrogradsky is used as the basic method. The calculation is adapted to tanks of a specific form.